Controlling corruption - Klitgaard, Robert E. (University of California Press, 1988)
Corruption is increasingly recognized as a preeminent problem in the developing world. Bribery, extortion, fraud, kickbacks, and collusion have resulted in retarded economies, predator elites, and political instability. In this lively and absorbing book, Robert Klitgaard provides a framework for designing anti-corruption policies, and describes through five case studies how courageous policymakers were able to control corruption.